Design and Biological Evaluation of Manganese‐ and Ruthenium‐Based Hybrid CO‐RMs (HYCOs). (23rd August 2019) - Ollivier, Anthony; Foresti, Roberta; El Ali, Zeina; Martens, Thierry; Kitagishi, Hiroaki; Motterlini, Roberto; Rivard, Michael
Abstract: Interest in the therapeutic effects of carbon monoxide (CO), a product of heme degradation catalyzed by the enzyme heme oxygenase‐1 (HO‐1), has led to the development of CO‐releasing molecules (CO‐RMs) for the controlled delivery of this gas in vivo. We recently proposed conjugating a cobalt‐based CO‐RM with various activators of nuclear factor erythroid 2‐related factor 2 (Nrf2), the transcription factor that regulates HO‐1 expression, in order to exploit the beneficial effects of exogenous and endogenous CO. In this study, we describe the preparation of hybrid molecules (termed HYCOs) conjugating a fumaric acid derivative as an Nrf2 activator to a Mn‐ or a Ru‐based CO‐RM known to be pharmacologically active. With the exception of an acyl‐manganese complex, these hybrids were obtained by associating the two bioactive entities by means of a linker of variable structure. X‐ray diffraction analyses and preliminary biological investigations are also presented. Abstract : CO operation : HYCOs are hybrid compounds consisting of an Nrf2/heme oxygenase‐1 (HO‐1) activator conjugated to a carbon‐monoxide‐releasing molecule (CO‐RM). This study reports the structure–activity relationships of various HYCOs derived from fumaric acid and bearing a Mn‐ or a Ru‐based CO‐releasing moiety. The synthesis and biological activities of these HYCOs are discussed.